Bound together for God and country: The binding moral foundations link unreflectiveness with religiosity and political conservatism. (1st March 2020) - Reynolds, Caleb J.; Makhanova, Anastasia; Ng, Ben K.L.; Conway, Paul
Abstract: Existing work suggests links between analytic cognitive style, endorsement of the binding moral foundations prioritizing sanctity, loyalty, and respect for authority, and individual differences in religiosity and conservatism. Yet, it remains unclear how these variables interrelate. In three new studies and a reanalysis of an open dataset, we find evidence that people who engage in less analytical thinking tend to endorse the binding (but not individualizing) moral foundations, which in may turn lead them to endorse various elements of religiosity and conservativism—including a) belief in God, b) intrinsic religious motivation, c) auxiliary religious beliefs (i.e., religious beliefs other than theism), d) reportedly engaging in religious practices, e) identification as politically conservative, and f) endorsement of both socially and fiscally conservative positions on political issues. These findings align with theories suggesting lower analytic cognitive style may be useful in socially dense environments where group cohesion is paramount. However, results do not rule out alternative frameworks, such as those treating moral values as a downstream product of political and religious attitudes.